The theatricalized hell of Smole's Antigone, Hieng's The Conqueror, and Zupančič's Electra's revenge - Toporišič, Tomaž (Slavia Centralis, 2025)
The present contribution focuses on three dramas whose authors turned to ancient myths and historical events to address contemporary ethical dilemmas. The dramas under scrutiny are: Antigone (1960) by Dominik Smole, The Conqueror (1970) by Andrej Hieng, and Electra’s Revenge (1988) by Mirko Zupančič. All three plays are marked by a Badiouan “passion for the real”. Smole explores the conflict between the individual and the state in the spirit of a post-war critical generation, Hieng draws attention to the dangers of colonialism and fanaticism, While Zupančič revives the myth of Electra to confront the impotence of truth in an era of ideological numbness. Despite bearing different aesthetics, all three dramas unite in their need to rethinking myth and history in a completely new way.
Keywords: post-war Slovenian drama; ancient myth; paraphrase; Dominik Smole; Andrej Hieng; Mirko Zupančič